Students with disabilities as partners: A case study on user testing an accessibility website - Brown, Kate; de Bie, Alise; Aggarwal, Akshay; Joslin, Ryan; Williams-Habibi, Sarah; Sivanesanathan, Vipusaayini (International Journal for Students as Partners, 2020)
While partnership is widely encouraged as an approach to advancing the inclusion of disabled postsecondary students, these collaborations are largely taking place between staff offices and failing to meaningfully integrate disabled students as partners. In this case study, we describe the successes and challenges of a pilot project where students and staff with and without disabilities worked together to user test our university’s accessibility website, to which faculty/staff are regularly directed for resources on making their teaching more accessible. We achieved our goal of compiling results into a report for decision-makers in order to advance campus-wide technological accessibility. Instead of primarily treating disabled students as lacking capacities and requiring programmatic intervention to succeed in the university, a partnership approach validates and draws on disabled students’ specific expertise and experience to make institutional change.